6.4k views
1 vote
Cos^-1(-x)=-Cos^-1x for -1<x<1 TRUE OR FALSE?

Cos^-1(-x)=-Cos^-1x for -1<x<1 TRUE OR FALSE?-example-1
User Regi
by
5.7k points

2 Answers

5 votes

Answer:

false

Explanation:

User Arlenis
by
5.7k points
1 vote

We are given


cos^(-1)(-x)=-cos^(-1)(x)

Firstly, we will simplify left side

and we will check whether it is equal to right side

Left side:

Let's assume y left side expression


y=cos^(-1)(-x)

now, we can take cos on both sides


cos(y)=cos(cos^(-1)(-x))

we can simplify it


cos(y)=-x

Right side:

Let's assume y left side expression


y=-cos^(-1)(x)

Multiply both sides by -1


-y=cos^(-1)(x)

now, we can take cos on both sides


cos(-y)=cos(cos^(-1)(x))

we can simplify it


cos(-y)=x


cos(y)=x

we can see that

both sides cos(y) value is different

so, this is FALSE.........Answer

User Mudassar Shaheen
by
5.6k points